GAMBARAN KEBIASAAN SARAPAN PADA ANAK SEKOLAH DASAR DI KABUPATEN BADUNG: DESCRIPTION OF BREAKFAST HABITS IN ELEMENTARY SCHOOL CHILDREN IN BADUNG REGENCY - Resiyanthi, Ni Komang Ayu; Suniyadewi, Ni Wayan (Bali Medika Jurnal, 2019)
Breakfast is important for fulfilling nutrition for everyone to start their activities. Breakfast is an eating and drinking activity that is carried out between getting up in the morning until 9 o'clock to fulfill a 15-30% of daily nutritional needs (Hardinsyah, 2012). The purpose of this study was to determine the description of breakfast habits in elementary school students in Badung Regency. This type of research is descriptive, which describes the breakfast habits of elementary school students in Badung Regency. The location of this research will be carried out in four elementary schools in Badung Regency, namely SD 1 Kuta, SD 3 Kuta, SD 2 Kuta and SD 1 Jagapati using 154 elementary students taken by purposive sampling. Of the 154 students studied it was found that the majority of elementary school students in Badung Regency are used to have breakfast as many as 120 people (77.9%). Most of the breakfast time is every morning 109 people (70.8%), most of the breakfast hours is at 6-7 in the morning as many as 149 people (96.8%), the majority of breakfast at home is as many as 152 people (98.7%) and most of the menus are alternating as many as 121 people (78.6%). It is recommended that health workers provide health education on the importance of a healthy breakfast both for students and parents because in addition to health, it is also very beneficial to improve student concentration and achievement.